1984
DOI: 10.1055/s-2008-1044245
|View full text |Cite
|
Sign up to set email alerts
|

Pelviureteric Obstruction in Children: The Effect of Pyeloplasty on99mTc-DTPA Uptake and Washout

Abstract: The renographies of 23 children, treated by means of dismembered pyeloplasty for unilateral pelviureteric obstruction, were analysed. Computerised 99mTc-DTPA renography was performed on each patient both preoperatively and on one or several occasions postoperatively. Of the 13 hydronephrotic kidneys, which had normal glomerular function preoperatively, 12 had also normal postoperative function. In a large proportion of those hydronephrotic kidneys which had reduced glomerular function preoperatively, the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They observed that hydronephrotic kidneys that had reduced glomerular function preoperatively improved after pyeloplasty. The improvement was more pronounced in the group of kidneys with severely reduced preoperative glomerular function [16].…”
Section: Discussionmentioning
confidence: 98%
“…They observed that hydronephrotic kidneys that had reduced glomerular function preoperatively improved after pyeloplasty. The improvement was more pronounced in the group of kidneys with severely reduced preoperative glomerular function [16].…”
Section: Discussionmentioning
confidence: 98%
“…Postoperative renal function has been studied less extensively and with conflicting results. Some inves tigators found no change in renal function after pyeloplasty [17,18], whereas others found an improvement [11,15,23], maximal already after 1-2 weeks [27], Experimental studies of renal function after release of partial ureteric obstruction, the most common type in children, have been performed only in adult animals. A moderate improvement, maximal within 6 weeks, was observed [ 13].…”
Section: Introductionmentioning
confidence: 99%
“…Most controversially, whether these patients should be aggressively treated with surgery or conservatively observed. The main goal in the treatment of UPJO is to preserve or improve renal function ( 19 , 20 ), we stressed no difference that conservative management of some patients with antenatally detected severe UPJO probably results in irreversible loss of function ( 21 ) and followed up with this study, which showed that immediate laparoscopic pyeloplasty accelerated the recovery of renal morphology in infants with severe UPJO-induced hydronephrosis. Immediate surgical intervention is effective and should be performed during this period.…”
Section: Discussionmentioning
confidence: 59%